Application of Digital Molding in Maxillofacial Prosthetics: A Narrative Review - Jahangiri, Maryam; Hakimaneh, Seyed Mohammad Reza; Bafandeh, Mohammad Amin; Bakhtiari , Fatemeh; Shayegh, Sayed Shojaedin (Galen Medical Journal, 2024)
Background: The use of digital tools and 3D molding has become very common in dentistry today. However, there are few studies on the possibility of using 3D imaging tools for molding maxillofacial defects. In this review study, we examine articles that have used digital molding tools instead of conventional methods for molding maxillofacial defects. Materials and Methods: In this study, all articles related to keywords of "3D imaging tools", "CT scans", "Maxillofacial Prosthesis" were collected and reviewed by searching PubMed and ISI Web of Science until 2024. Then, the materials were classified into the following topics: the use of intraoral scanners in molding for maxillofacial prostheses, the use of facial scanners in molding for maxillofacial prostheses, the use of CT scans in molding for maxillofacial prostheses, and the use of new digital methods in molding for ocular, nasal, ear prostheses, maxillary and mandibular obturators, soft palate defects, and nasoalveolar molding prostheses, and were examined in detail. Results: This study showed that depending on the type of defect, specific types of digital molding tools can be used to the greatest advantage. Intraoral scanners can be used in the construction of nasoalveolar moldings, obturators, cleft palate, and ear prostheses. Facial scanners have the highest accuracy for molding defects in the middle third of the face. Facial scanners are helpful in midface defects, and in the construction of ocular and nasal prostheses. The main use of CBCT molding is in molding the patient's palate for the design and construction of obturators. For mandibular molding, the use of intraoral scanners is much better than other methods. Moreover, even in cases where the patient has mild to moderate trismus after mandibulectomy, the use of intraoral scanners has acceptable accuracy.